The young generation and their struggle for a place in society - Khamisah, Ali (Pusat Penerbitan dan Teknologi Pendidikan UKM, Bangi Selangor, 2004)
This paper discusses the views of 30 young people on the positive and negative aspects of Rakan Muda Programmes. The findings show that young people who joined the Rakan Muda Programme tend to support the majority views that youths are the problem rather than being victims in today’s Malaysia. Being Rakan Muda members, they gained not only life skills but also a better understanding on how to behave according to the accepted norms and values in society. Directly or indirectly, all respondents confirmed the majority beliefs that require young people to conform more closely to the law and social order, and perceived it is a mistake to oppose the system. In relation to families, a research finding shows that respondents and their parents have less stormy relationships than that might be generally imagined. Parents remain an important influence throughout the respondents’ transition to adulthood, helping them to form their sense of self and shape their future / life choices. Peer pressure may become more important for young people whose access to parental influences is impaired. A strong and consistent finding among all participants is that they have been given too little scope to express the needs and problems in their life. These young people believe that they are not totally responsible for their misbehaviors, and argue that the cause of this is the fact that there are not enough facilities available to cater for their needs in the society. From this position, they argue that every member in the society has to play a part in solving the youth problems.